In an effort to advance Pemanfaatan Media Digital Untuk Meningkatkan Daya Saing Usaha Pada Bimbel Smart Club (Jurnal Sosial & Abdimas, 2020)
In an effort to advance the industry in the era of globalization it seems less popular if a business has not used information technology that is currently fast. Digital marketing is one marketing tool that is widely used by entrepreneurs both at the starup level and established businesses to increase market share and business competitiveness. The purpose of this study is to examine how the role of using digital media to improve business competitiveness in Bimbel Smart Club. The method applied in this research is descriptive research method by conducting surveys and interviews and then assisted with literature review to provide alternative solutions. The results of this study explain that the use of digital media can simplify and speed up the transaction process. This will certainly make it easier for the company to reach a wider target market and have an impact on the company's efficiency. Keyword: Digital Marketing, Business Competitiveness, Human Resources